Intention to consume news via personal social media network and political trust among young people: The evidence from Hong Kong - Zhang, Youliang; Tian, Zhen; Zhou, Ziwei; Huang, Jing; Zhu, Alex Yue Feng (Frontiers in Psychology, 2023)
Assessing the effect of different media sources on political trust provides an overall picture of the role of the current media landscape in influencing the legitimacy of political institutions. Thus, as a part of the present study, a cross-lagged model was developed and tested by applying it to a three-wave dataset obtained by surveying young people in Hong Kong in order to evaluate the unique impact of news consumption via personal social networks on political trust. The results obtained after controlling for the impact of other news channels and respondents’ prior political interest indicate that their political trust was most significantly affected by information obtained from friends and family through their personal social media network. These research findings indicate that media exhibits a relatively weak effect on political trust, which is primarily influenced by selection, indicating that policymakers do not have to be concerned with online exchange of information that is critical of the government. Moreover, they suggest that, when it comes to developing political trust throughout the society, conflicts resulting from opposing views are better than ignorance.